2006
DOI: 10.1074/jbc.m600879200
|View full text |Cite
|
Sign up to set email alerts
|

The Estrogen-responsive B Box Protein Is a Novel Regulator of the Retinoid Signal

Abstract: Retinoic acid (RA) induces growth arrest, cell death, and differentiation in many human cancer cells in vitro and has entered routine clinical use for the treatment of several human cancer types. One mechanism by which cancer cells evade retinoid-induced effects is through repression of retinoic acid receptor ␤ (RAR␤) gene transcription. The RA response element ␤ (␤RARE) is the essential DNA sequence required for retinoid-induced RAR␤ transcription. Here we show that the estrogen-responsive B box protein (EBBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 53 publications
1
32
0
2
Order By: Relevance
“…TRIM16 is a member of the RING-B box-coiled-coil protein family; its biological function has not been well characterized. However, evidence seems to suggest that TRIM16 may play a role in the response of tissues to differentiating agents (63), have a pivotal role in the retinoid anticancer signal (64,65) and play a role in innate immunity by enhancing the alternative secretion pathway of interleukin 1β (66). AKR1C3 converts adrenal androgens such as androstenedione and dehydroepiandrosterone into intraprostatic testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM16 is a member of the RING-B box-coiled-coil protein family; its biological function has not been well characterized. However, evidence seems to suggest that TRIM16 may play a role in the response of tissues to differentiating agents (63), have a pivotal role in the retinoid anticancer signal (64,65) and play a role in innate immunity by enhancing the alternative secretion pathway of interleukin 1β (66). AKR1C3 converts adrenal androgens such as androstenedione and dehydroepiandrosterone into intraprostatic testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM16 is an estrogen responsive gene also known as estrogen-responsive B box protein (EBBP), initially described for its involvement in keratinocyte differentiation [99] and retinoid metabolism [100]. Recently a role for this protein in regulating secretion of the proinflammatory cytokine IL-1β has been reported [101].…”
Section: Autoinflammatory Diseases -Inflammasome Regulation By Trim Fmentioning
confidence: 99%
“…Gene ontology analysis (http://david.abcc.ncifcrf.gov/) showed that the largest class of target genes are involved in transcription regulation, for example, transcription factors such as Hoxa10 and Hoxd13 and the RAR coactivators Hmga1 (39), Trim16 (12), and Top2b (23). One of the main functions of RARs is therefore to regulate other transcriptional networks (Fig.…”
Section: Identification Of Rar Target Genes In Mefs To Identify Rar mentioning
confidence: 99%